A barnavirus sequence mined from a transcriptome of the Antarctic pearlwort Colobanthus quitensis - Nibert, Max L. (2018)
Because so few viruses in the family Barnaviridae have been reported, we searched for more of them in public sequence databases. Here, we report the complete coding sequence of Colobanthus quitensis associated barnavirus 1, mined from a transcriptome of the Antarctic pearlwort Colobanthus quitensis. The 4.2-kb plus-strand sequence of this virus encompasses four main open reading frames (ORFs), as expected for barnaviruses, including ORFs for a protease-containing polyprotein, an RNA-dependent RNA polymerase whose translation appears to rely on − 1 ribosomal frameshifting, and a capsid protein that is likely to be translated from a subgenomic RNA. The possible derivation of this virus from a fungus associated with C. quitensis is discussed.